The effect of internal corporate governance mechanisms toward corporate social responsibility disclosures: evidence found in Indonesia listed mining industry - Tarigan, Josua; Antonius, Jacky (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
This research attempts to scrutinize the impact of managerial ownership, board independence, and female directors on board toward the Corporate Social Disclosure Index (CSID) to observe how a company's internal corporate governance mechanism affects the intensity of CSR disclosure. CSR disclosure is measured by a standardized approach of GRI G4 framework as the reporting standard. CSR Disclosure analysis was undergone on 34 listed mining companies in Indonesia during the observation years of 2016 to 2020. It is found that managerial ownership significantly negatively impacts a firm's sustainability disclosure. In contrast, the remaining variables consisting of board independence and female directors on board have an insignificant effect on a firm's sustainability disclosure, with firm size, firm leverage, and firm profitability acting as the control variables. This study expands previous literature on the CSR disclosure level with only the sole impact of board characteristics by adding another managerial ownership variable besides independent and female board members. Furthermore, the observation period has also been extended from 2016 to 2020 to accommodate the changing of the board members.